STATISTICAL ANALYSIS OF THE RELATIONSHIP BETWEEN MONTHLY AIR TEMPERATURE AND RELATIVE HUMIDITY CHANGE IN THE TERRITORY OF THE REPUBLIC OF UZBEKISTAN, AND CASES OF INFECTION OF THE COVET-19 - Irgashev Suyundik Uktamovich (Лучшие интеллектуальные исследования, 2023)
Abstract: In this state and basic data, provided by Yandex Roshydrometer and Johns Hopkins University & Medicine, a statistical analysis was carried out regarding changes in temperature and relative humidity in the territory of the Republic of Uzbekistan and cases of coronavirus infection. Covet-19provoditsya .